Implementing Multisensory Approach to Overcome Reading Difficulties in 4th Grade Students - Marsalina Mitak; Fitriah; Mastoh Chesoh (The Indonesian Institute of Science and Technology Research, 2023)
Reading is one of the language skills that students must possess. The purpose of this study is to address difficulties in learning to read through multisensory methods for participants. The study was conducted at SD Inpres Lisabheto (a public elementary school), Sikka Regency. The research method employed a qualitative approach with a descriptive method. The subjects targeted in the study were fourth-grade students. To gather data, the researcher used observation techniques, documentation, and reading practice tests. The results of the study obtained by the researcher through the use of multisensory methods on fourth-grade students who still experienced difficulties in learning to read using visual (sight), auditory (hearing), tactile (touch), and kinesthetic (movement) sensory tools. The use of multisensory methods proved to be an improvement in the reading learning ability of fourth-grade students who still struggle with reading. The study found that implementing the multisensory approach in reading instruction had a positive impact on the reading speed of fourth-grade students at Inpres Lisabheto Elementary School. The guidance provided by the classroom teacher and researcher was effective in improving the students' ability to memorize the alphabet, spelling, combining words, and recognizing symbols in writing. The use of the multisensory approach also increased the students' confidence and motivation to become more active and interactive in their learning.